Homeless Dogs and Melancholy Apes : Humans and Other Animals in the Modern Literary Imagination - Brown, Laura, 1949- (Book collections on Project MUSE., 2010)
"Writers of this first age of the rise of the animal in the modern literary imagination used their nonhuman characters--from the lapdogs of Alexander Pope and his contemporaries to the ill-mannered monkey of Frances Burney's Evelina or the ape-like Yahoos of Jonathan Swift--to explore questions of human identity and self-definition, human love and the experience of intimacy, and human diversity and the boundaries of convention. Later writers continued to use imaginary animals to question human conventions of form and thought. Brown pursues this engagement with animal-kind into the nineteenth century--through works by Mary Shelley, Charles Dickens, and Elizabeth Barrett Browning--and into the twentieth, with a concluding account of Paul Auster's dog-novel, Timbuktu. Auster's work suggests that--today as in the eighteenth century--imagining other animals opens up a potential for dissonance that creates distinctive opportunities for human creativity."--Jacket.